2016
DOI: 10.7717/peerj.1566
|View full text |Cite
|
Sign up to set email alerts
|

Experimental modulation of external microbiome affects nestmate recognition in harvester ants (Pogonomyrmex barbatus)

Abstract: Social insects use odors as cues for a variety of behavioral responses, including nestmate recognition. Past research on nestmate recognition indicates cuticular hydrocarbons are important nestmate discriminators for social insects, but other factors are likely to contribute to colony-specific odors. Here we experimentally tested whether external microbes contribute to nestmate recognition in red harvester ants (Pogonomyrmex barbatus). We changed the external microbiome of ants through topical application of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 25 publications
(35 reference statements)
0
26
0
Order By: Relevance
“…, Dosmann et al. ) or provide protection through production of antimicrobial compounds (Promnuan et al. , Sen et al.…”
Section: Introductionmentioning
confidence: 99%
“…, Dosmann et al. ) or provide protection through production of antimicrobial compounds (Promnuan et al. , Sen et al.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, colony identity is conveyed by a highly diverse set of CHCs, and intraspecific and interspecific invaders from other colonies are detected and defended against as a consequence of having a different CHC blend than the blend associated with a particular nest/colony (4). In addition, other non-CHC olfactory stimuli play important roles in ant chemical ecology as alarm, trail, or recognition pheromones and are often found in ant exocrine glands (5) and in the microbiota of the ant cuticle (6).…”
mentioning
confidence: 99%
“…Such effects may result from the direct actions of the antibiotic or from indirect effects, such as changes in host metabolism or production of nutrients sustaining cuticular bacterial growth. In Drosophila , cuticular microbes have been hypothesized to affect chemical profiles by using CHC as a carbon source or a substrate for degradative enzymes (12), and previous research on Pogonomyrmex ants showed that topical antibiotic administration can alter CHC profiles, confirming a possible role of surface microbes in CHC profile determination (18). However, the same kind of antibiotic treatment applied on Acromyrmex subterraneus did not affect CHC profiles (19).…”
Section: Discussionmentioning
confidence: 97%
“…In Pogonomyrmex barbatus harvester ants, individuals with experimentally-augmented cuticular microbiomes are rejected by nestmates more than controls, whereas antibiotic-treated individuals are not. This suggests that cuticle-dwelling microbes influence nestmate recognition dynamics (18). Contrarily, however, topical antibiotic administration on Acromyrmex subterraneus leafcutter ants does not affect cuticular hydrocarbon profiles (19).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation